Extensional forearc structures at the transition from Alaska to Aleutian Subduction Zone: slip partitioning, terranes and large earthquakes - Kahrizi, Amin; Delescluse, Matthias; Chamot-Rooke, Nicolas; Pubellier, Manuel; Bécel, Anne; Shillington, Donna; Nedimović, Mladen; Bulois, Cédric (Comptes Rendus. Géoscience)
The Unimak and Shumagin segments of the Alaska Aleutian Subduction Zone show extensional deformation of the forearc since the Miocene. Using legacy seismic profiles and modern multichannel seismic data, we update the structural map of the area, focusing on the intersection between trench-parallel, landward-dipping normal faults rooting in the plate interface and trench-oblique to trench-perpendicular normal faults, all showing signs of recent activity. We investigate for the first time the origin of the trench-parallel extension and explain the horsetail geometry of the Central Sanak Basin as the termination of a slip-partitioning right-lateral strike slip fault. Re-analysis of subduction zone thrust earthquakes slip vectors indicates a possible onset of slip partitioning in the vicinity of the Central Sanak Basin. In the hypothesis of a continuum of deformation, finite deformation from normal fault offsets show a slow sliver motion of less than 1 mm/yr, which is below the resolution of GNSS measurements. Both trench oblique and trench parallel faults have been cited as reactivated terrane sutures, the presence of which may act as upper-plate weaknesses needed to allow slip partitioning in a context of low convergence obliquity. Weak landward-dipping normal faults rooting in the plate interface have also been linked to the tsunamigenic rupture of the shallow plate interface. We infer that the trench parallel Unimak Ridge, associated with the 1946 Mw 8.6 tsunami earthquake, is the last expression of terrane sutures reactivation before their westward vanishing in the more recent Aleutian arc.